Quantity and Quality of Parental Utterances and Responses to Children With Hearing Loss Prior to Cochlear Implant. (December 2019) - Su, Pumpki L.; Roberts, Megan Y.
This study investigated the extent to which parental language input to children with hearing loss (HL) prior to cochlear implant (CI) differs from input to children with typical hearing (TH). A 20-min parent–child interaction sample was collected for 13 parent–child dyads in the HL group and 17 dyads in the TH group during free play. Ten minutes were transcribed and were coded for four variables: (a) overall utterances, (b) high-quality utterances, (c) utterances in response to child communicative acts (i.e., overall responses), and (d) high-quality utterances in response to child communicative acts (i.e., high-quality responses). Differences were detected for both quantity and quality of parental language input across the two groups. Early language skills correlated with three out of the four parental variables in both groups. Post hoc analyses suggested that the lower rate of high-quality responses in parents of children with HL could be attributed to lower intelligibility of child communication.